Firm location determinants: Empirical evidence for France - Nadia Rocha (Graduate Institute of International and Development Studies, 2008)
This paper analyzes the effects of local externalities on the probability of starting a new economic activity. We use firm-level data and geographic information on French zip-codes for 1993-2002. Poisson and Negative Binomial panel data models are estimated as they naturally allow for large sets of location choices with frequent zero outcomes and control for unobserved zip-code heterogeneity. To measure the geographic extent of location externalities we compute localization, urbanization and congestion variables for neighboring regions. We separately analyze the scale effects stemming from exporting and non-exporting firms. Our results show that agglomeration economies at zip-code level strongly effect the location decision of industrial establishments and find the presence of agglomeration shadows, one of the core predictions of the standard New Economic Geography formulations.
Keywords: R30; C50; L60; 330; Firm Location; Agglomeration Economies; Agglomeration Shadows; Betriebliche Standortwahl; Unternehmensgründung; Ballungsraum; Neue ökonomische Geographie; Schätzung; Frankreich